Functionally relevant proteins in Plasmodium falciparum host cell invasion (2017)
A totally effective, antimalarial vaccine must involve sporozoite and merozoite proteins (or their fragments) to ensure complete parasite blocking during critical invasion stages. This Special Report examines proteins involved in critical biological functions for parasite survival and highlights the conserved amino acid sequences of the most important proteins involved in sporozoite invasion of hepatocytes and merozoite invasion of red blood cells. Conserved high activity binding peptides are located in such proteins' functionally strategic sites, whose functions are related to receptor binding, nutrient and protein transport, enzyme activity and molecule-molecule interactions. They are thus excellent targets for vaccine development as they block proteins binding function involved in invasion and also their biological function. © 2017 Future Medicine Ltd.